The Sacred Mirror : Evangelicalism, Honor, and Identity in the Deep South, 1790-1860 - Elder, Robert, 1981- (Book collections on Project MUSE., 2016)
Most histories of the American South describe the conflict between evangelical religion and honour culture as one of the defining features of southern life before the Civil War. The story is usually told as a battle of clashing worldviews, but in this book, Robert Elder challenges this interpretation by illuminating just how deeply evangelicalism in Methodist, Baptist, and Presbyterian churches was interwoven with traditional southern culture.